SAUCES PRODUCTS BASED ON HOMOGENATE OF THE FRUITS OF SORBUS AUCUPARIA - Ksenia Nikolaevna Nitsievskaya (Современная наука и инновации, 2022)
The paper Presents a review of scientific and technical documentation for the sauce products. Disadvantages of these methods are defined as the use of high-temperature modes of processing plant raw materials, thereby reducing the nutritional value of the finished product, as the use of preservatives (in the form of citric acid and sugar) and stabilizers (in the form of starches), the use of alcohol-containing components, which limits the purpose of the product for food purposes.